Towards Surface‐Enhanced Homogeneous Catalysis: Tailoring the Enrichment of Metal Complexes at Ionic Liquid Surfaces - Hemmeter, Daniel (2025)
When talking about homogeneous catalyst systems, it has long been assumed that the system at hand consists of a transition metal complex in solution with the liquid interface representing the composition of the bulk solution. Now, in light of considerable developments in the study of metal complexes dissolved in ionic liquids with their negligible vapor pressures, more detailed studies of the composition at the liquid/gas interface became possible. These investigations revealed pronounced surface enrichment and segregation effects of high relevance for practical applications. This article reviews recent advancements in tailoring the interfacial composition of ionic liquid-based catalytic systems. A particular focus is dedicated to surface enrichment phenomena, and a variety of parameters are presented for deliberate control of the local concentration of the complexes at the surface, that is, the nature of the ligands, the bulk concentration, the temperature, and the nature of the IL solvent. As experimental methods, angle-resolved X-ray photoelectron spectroscopy (ARXPS) and vacuum-based pendant-drop surface tension measurements were applied. The reviewed results are intended to provide the basis for the advancement of catalytic systems with high surface areas, such as in supported ionic liquid phase (SILP) catalysis, where the interface design is directly interconnected with catalytic performance.